Predictive Value of the Postural Difference in Antero-Posterior Diameter of Renal Pelvis on Ultrasonography of Unilateral Ureteropelvic Junction Obstruction in Determining the Need For Surgery - Bijay Kumar Suman; Ram Jeewan Singh; Aditya Arvind Manekar; Subrat Kumar Sahoo; Bikasha Bihari Tripathy; Manoj Kumar Mohanty; Sudipta Mohakud (Wolters Kluwer Medknow Publications, 2024)
Background: Ureteropelvic junction obstruction (UPJO) is the most common cause of antenatal hydronephrosis. Although majority of them improve with time, none of the existing diagnostic modalities can accurately predict which hydronephrotic kidney is at the risk of progressive renal damage and will benefit from early surgery. Postural variations in the anteroposterior pelvic diameter (APPD) of the hydronephrotic kidney in children during follow-up postnatal ultrasonography (USG) reflect the intrapelvic tension, which might help in predicting the need of surgery amongst these patients. Materials and Methods: We designed this prospective observational study in all unilateral UPJO patients on postural variation in the APPD of renal pelvis on ultrasonography. The mean age of all patients were 2.15 years (0-5 years) and managed at our institute at All India Institute of Medical Sciences, Bhubaneswar. The study duration was from July 2019 to May 2021. The management of these patients was done as per the standard institutional protocol and there was no deviation due to inclusion in this study. We documented the variations in postural APPD both amongst the conservatively managed group and the surgically managed group of patients. Linear correlation between two continuous variables was explored using Pearson's correlation (if the data were normally distributed) and Spearman's correlation (for non-normally distributed data). Results: We found a higher prone APPD than supine APPD in all these patients indicating the obstruction at ureteropelvic junction. However, in the surgical group, there was less variation in the postural APPD compared to the conservative group, and when there was no variation in the postural APPD, the need of surgery was 100%. The limitation of our study was the small sample size (n = 36). A study involving a larger population or involving multiple institutions may further add significance to our findings. Conclusion: We found less postural variation in APPD on USG to be more likely associated with severe UPJO requiring early surgery. This may indicate a non-compliant renal pelvis. However, it was statistically not significant.